Healthcare Providers’ Interest in Receiving Sexually Transmitted Infection Training—DocStyles Survey, United States, Fall 2024 - Guoyu Tao; Alexandra Coor; Lindley A. Barbee (Sexually Transmitted Diseases, 2026)
Background. There is limited evidence assessing healthcare providers’ interest in sexually transmitted infection (STI) training in the United States (US). Methods. Five STI-related questions were included in the Fall 2024 DocStyles survey, a US national, semi-annual web-based survey of healthcare providers. The study sample consisted of 1,501 providers: 1,001 primary care physicians (PCPs); 250 obstetricians/gynecologists (OB/GYNs); and 250 nurse practitioners and physician assistants (NP/PAs). Bivariate analyses and multiple logistic models were used to identify factors statistically associated with interest in STI training (p10% of their patients with STI services (36.9% among PCPs, 88.4% among OB/GYNs, and 35.6% among NP/PAs). Only 17.1% reported receiving specialized STI training beyond residency or fellowship. Nearly half (48.2%) reported to be very or extremely interested in receiving STI training (47.6% of PCPs, 56.0% of OB/GYNs, and 42.8% of NP/PAs). Providers were more likely to be interested in STI training if they were female, Hispanic, non-Hispanic Black, or non-Hispanic Asian, had 3–19 years of practice (compared with 30 or more years), cared for more than 50 patients per week, provided >10% of their patients with STI services (versus less than 10%), and had received specialized STI training beyond residency or fellowship. Conclusion. Our findings suggest ongoing demand for STI training for US healthcare providers. More targeted and effective outreach strategies are needed to reach providers who may be less likely to access this training, including primary care physicians and nurse practitioners/physician assistants.